2008
DOI: 10.1007/s10201-008-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and pigment type composition of picocyanobacteria in Barguzin Bay, Lake Baikal

Abstract: In Lake Baikal, picocyanobacteria are the most important primary producers during the summer. Freshwater picocyanobacteria are discriminated into either the phycoerythrin (PE)-rich or the phycocyanin (PC)-rich types according to their pigment composition. The distributions of these two types of picocyanobacteria were investigated in Barguzin Bay. The PC-rich type accounted for [98% of the total picocyanobacteria at the station near the shore of the bay where river water flows directly in. In the offshore area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Similar result was also found in Suruga Bay, Japan (Shimada et al, 1995). This group was phycocyanobilin (PC)-rich syn (Shimada et al, 1995) and was introduced into the marine water column by river inputs, which mainly consisted of Synechococcus from the river freshwater (Katano et al, 2008;Olson et al, 1988).…”
Section: Spatial Distribution Of Picophytoplankton and Nanophytoplanksupporting
confidence: 83%
“…Similar result was also found in Suruga Bay, Japan (Shimada et al, 1995). This group was phycocyanobilin (PC)-rich syn (Shimada et al, 1995) and was introduced into the marine water column by river inputs, which mainly consisted of Synechococcus from the river freshwater (Katano et al, 2008;Olson et al, 1988).…”
Section: Spatial Distribution Of Picophytoplankton and Nanophytoplanksupporting
confidence: 83%
“…Reasons for this may be the presence of favourable nutrient, temperature or light conditions, or ecological niches in a wider sense (Postius & Ernst, ), for example, substrates or biofilms (Becker et al ., ). Furthermore, near‐shore lake water may provide better growth conditions for PC‐rich APP cells, as was demonstrated in Lake Baikal (Katano et al ., ). Pelagic PC‐rich Synechococcus isolates from Lake Constance were shown to respond to N‐deprivation by exudation of high‐molecular weight polysaccharides, a feature not detectable in PE‐rich strains (Postius & Böger, ).…”
Section: Resultsmentioning
confidence: 97%
“…This may also hold true in the littoral areas of lakes, where high light conditions may lead to the dominance of certain PC‐rich Synechococcus genotypes (e.g. in biofilms on macrophytes in the surf zone), and where the presence of certain nutrient (Katano et al ., ) or physical conditions such as temperature regimes (Sommer, ; Schweizer, ; Gaedke & Weisse, ), and substrates (Becker et al ., ) might provide suitable conditions in the littoral habitat as well.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been suggested that PC-type Synechococcus strains have a greater ability to deal with salinity variation than marine PE-type Synechococcus (4,55). Although high abundance of PC-type Synechococcus strains was often found in estuarine waters (56,57), only a few studies have reported their community composition at the molecular level. In this study, we found that PC-type Synechococcus assemblages in Hong Kong estuarine waters were composed of marine-source Synechococcus (subcluster 5.2, represented by Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%